The family book of manners - Hartley, Hermine; Hartley, Al (Valenzuela, Philippines : Christian Literature Crusade, 1999)
Provides guidance on appropriate behavior in a wide variety of situations, such as eating out, polite conversation, interpersonal relations, family matters, and more.
Keywords: Etiquette for children and teenagers; Etiquette; Conduct of life